Covid-19 and Race: News Coverage of Structural Racism and The Role of John Henryism and Racial Weathering in Bame Covid-19 Deaths. Issue 2 (3rd April 2022) - Sikka, Tina
Abstract : In this article, I use media analysis and materialist theory to examine two overlooked factors that have emerged out of the startling statistics around race and Covid-19. These are 1. John Henryism and 2. racial weathering. I argue that missing from media coverage are the manifold confounding and unexplored ways in which race and racism are enacted by Covid wherein the disease itself is understood as existing within a network of interacting human and non-human forces and structures. My argument is that the tendency for the media to confine itself to focusing on how social determinants impact the health of racialised groups, while important, has meant that other, more granular enactments of race and injustice have been ignored.